2020
DOI: 10.3389/fonc.2020.574861
|View full text |Cite
|
Sign up to set email alerts
|

Sapitinib Reverses Anticancer Drug Resistance in Colon Cancer Cells Overexpressing the ABCB1 Transporter

Abstract: The efficacy of anti-cancer drugs in patients can be attenuated by the development of multi-drug resistance (MDR) due to ATP-binding cassette (ABC) transporters overexpression. In this in vitro study, we determined the reversal efficacy of the epidermal growth factor receptor (EFGR) inhibitor, saptinib, in SW620 and SW720/Ad300 colon cancer cells and HEK293/ABCB1 cells which overexpress the ABCB1 transporter. Sapitinib significantly increased the efficacy of paclitaxel and doxorubicin in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…The elevated sensitivity to paclitaxel from MCTSs generated from SW620/Ad300‐ABCB1ko and SW620‐ABCB1ko cells were shown by loss of integrity and loosely associated dead cells at the outer layer after 48 and 72 h of exposure, which was consistent with the appearance of paclitaxel‐treated MCTSs from SW620/Ad300 cells reported by Gao et al. 37 …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The elevated sensitivity to paclitaxel from MCTSs generated from SW620/Ad300‐ABCB1ko and SW620‐ABCB1ko cells were shown by loss of integrity and loosely associated dead cells at the outer layer after 48 and 72 h of exposure, which was consistent with the appearance of paclitaxel‐treated MCTSs from SW620/Ad300 cells reported by Gao et al. 37 …”
Section: Discussionsupporting
confidence: 87%
“…Cells were prepared for antibody binding by undergoing fixation, permeabilization, and serum blocking processes as previously described. 37 Cells were then incubated with the monoclonal antibody against ABCB1 (1:1000 dilution) overnight at 4°C followed by incubation with Alexa Flour 488‐linked secondary antibody (1:1000 dilution) for 2 h at room temperature. The nuclei of cells were visualized by counterstaining using DAPI.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, four out of the six FDA-approved quinazolines are EGFR inhibitors: gefitinib, erlotinib, afatinib, and lapatinib [ 33 , 34 ]. It was also reported that the EGFR and HER2/3 inhibitor sapitinib, which contains a quinazoline moiety, showed chemosensitizing effect on resistant CRC cells by downregulation of the ABCB1 transporter [ 35 ]. A previously synthetized novel quinazoline derivative [ 36 ] will be used in this study (named HAA 2020 , Figure 1 C).…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of reports specified structure-based retrospective computational approaches, in which observed biological effects of compounds were underpinned mostly through molecular docking experiments with cryo-EM structures or homology models. Most pronounced are, again, ABCB1 [37] , [38] , [39] , [40] , [41] , [42] and ABCG2 [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] . Less- or under-studied ABC transporters are barely reflected in the literature.…”
Section: Introductionmentioning
confidence: 96%